Microbiological characteristics of hypermucoviscous Klebsiella pneumoniae isolates from different body fluids: Microbiological Characteristics of hvKP Isolates - Xiao, Xiumei; Yao, Bei; Zhou, Qingtao; Zhang, Jie (The Journal of Infection in Developing Countries, 2017)
Introduction: Reports of hypermucoviscous Klebsiella pneumoniae (hvKP) isolated from fluids other than blood or abscess are rare. The aim of the study was to compare clinical and microbiological characteristics of hvKP found in blood or abscess fluid with those isolated from other loci. Methodology: A total of 24 non-repetitive hvKP isolates were collected from January 2013 to June 2014 from patients with hvKP infections. There were 15 in Group 1 (fluid other than blood or abscess) and 9 in Group 2 (blood or abscess fluid). Medical records of all patients were reviewed. Capsular polysaccharide (CPS) typing, virulence factor determination, and multilocus sequence typing (MLST) of hvKP isolates were performed. Results: Seventeen sequence types (STs) and 6 capsular serotypes were identified. Type K2CC65 was most commonly identified in Group 1 and type K2CC86 in Group 2. Deletion of pLVPK-derived loci were found in K2 and non-K1/K2 hvKP strains. Two virulent genes, fimH and ycfM, were identified more frequently in Group 2 than in Group 1. There was no difference in the frequency of other virulent genes or serotypes in the two groups. Two imipenem resistant hvKP isolates (cr-hvKP) were found in non-blood or abscess samples. Conclusions: hvKP isolated from different body fluids had similar clinical and microbiological characteristics. cr-hvKP identified in non-blood or abscess samples should raise our attention to the challenging situation and management of hvKP infection.